2007
DOI: 10.1093/ecam/nem168
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Plectranthus amboinicus in the Treatment of Rheumatoid Arthritis

Abstract: Plectranthus amboinicus (P. amboinicus) is a folk herb that is used to treat inflammatory diseases or swelling symptoms in Taiwan. We investigated therapeutic efficacy of P. amboinicus in treating Rheumatoid Arthritis (RA) using collagen-induced arthritis animal model. Arthritis was induced in Lewis rats by immunization with bovine type II collagen. Serum anti-collagen IgG, IgM and C-reactive protein (CRP) were analyzed. To understand the inflammation condition of treated animals, production of TNF-α, IL-6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…The saturated fatty acids ranged from 17.9 to 36.7% while the monounsaturated fatty acids ranged between 13.4 and 28.1%. Wheat bran rich in PUFA, essential fatty acids were 56% in DWR 1006 variety, followed by CWB at 55%, which are comparable with earlier reports of Chang et al (2010). Presence of high amount of linoleic acid (18:2) as observed in WB oil is a good source of x-6 fatty acids along with the small amount of x-3 fatty acids.…”
Section: Fatty Acid Composition Of Different Varieties Of Wheat Bransupporting
confidence: 88%
“…The saturated fatty acids ranged from 17.9 to 36.7% while the monounsaturated fatty acids ranged between 13.4 and 28.1%. Wheat bran rich in PUFA, essential fatty acids were 56% in DWR 1006 variety, followed by CWB at 55%, which are comparable with earlier reports of Chang et al (2010). Presence of high amount of linoleic acid (18:2) as observed in WB oil is a good source of x-6 fatty acids along with the small amount of x-3 fatty acids.…”
Section: Fatty Acid Composition Of Different Varieties Of Wheat Bransupporting
confidence: 88%
“…RA is a type of chronic, systemic autoimmune disease which has the predominant feature of symmetrical polyarthritis, and anti-inflammatory analgesic symptomatic treatments, which would delay the development of the disease, offer the major therapeutic options (2,16). Local inflammation of the joints is a key link in the process of its pathogenesis; bone loss or damage caused by inflammation is the result of changes to the joints in RA, and symptoms of pain associated with joint swelling are often the most severe symptoms of which the patient complains (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that, in the limb joints of a mouse RA model, the mice have the same T-cell receptor (TCR) Vβ clone type T cells. However, as the development of the disease progresses, the numbers of this type of clone T cell increase gradually, whereas those of other TCR Vβ clone type T cells are gradually reduced: Therefore, this T cell clone type may be associated with the pathological changes of arthritis (1)(2)(3). Collagen-induced arthritis (CIA) is associated with pathogenetic and pathological changes that are similar to those of RA, and so CIA is often used as a model of human RA (4).…”
Section: Introductionmentioning
confidence: 99%
“…The plant is also used to treat gastritis and intestinal spasms [80], stomach pain, nausea, vomiting and is used as purgatives, carminatives and as anthelmintic [81], antioxidant activity [82] Punica granatum Sore throat, stomach problems, uterine problems Sore throat…”
Section: Indigestionmentioning
confidence: 99%